Pellet patented technology for fast and distinct visual detection of cholinesterase inhibitors in liquids - Vysloužil, Jakub; Vetchý, David; Zeman, Jiří; Farsa, Oldřich; Franc, Aleš; Gajdziok, Jan; Vysloužil, Jan; Ficeriová, Katarína; Kulich, Pavel; Kobliha, Zbyněk; Pitschmann, Vladimír (Journal of pharmaceutical and biomedical analysis, 2018)
The main objective of the presented research was to prepare an innovative carrier as a filler for detection tubes in the form of double-coated pellets with a very significant color transition during the detection of cholinesterase inhibitors such as nerve agents, organophosphorus or carbamate insecticides in liquids that is observable visually and also spectrophotometrically at 412 nm. The pellet cores were prepared by the extrusion/spheronization method. Consecutively, two different coats were applied on the pellet cores in the coating device using the Wurster column method. To increase the color change intensity, the second semipermeable coat based on Eudragit® RL was applied on top of the first coat, which was formed by butyrylcholinesterase immobilized in hydroxypropyl methylcellulose. Prepared samples differing in thickness of the second coat were evaluated for their quality parameters, enzymatic activity and inhibition. The detection mechanism was based on the standard Ellman's colorimetric reaction. It was observed that the semipermeable coat prevented leaching of the enzyme into the solution and led to an increased intensity of color transition from white - yellow to white - deep yellow/orange, thus enabling a more accurate visual detection. This system allows easy, rapid and safe identification of cholinesterase inhibitors in liquids, especially chemical warfare agents.
Keywords: Spectrophotometry; cholinesterasové inhibitory; kolorimetrie; Colorimetry; polymery; spektrofotometrie; Hypromellose Derivatives; roztoky; Polymers; butyrylcholinesterasa; deriváty hypromelózy; Butyrylcholinesterase; Solutions; Cholinesterase Inhibitors